Surviving triple negative breast cancer : hope, treatment, and recovery - Prijatel, Patricia, 1945- (Oxford University Press, 2013)
"After her diagnosis of hormone-negative breast cancer, health journalist Patricia Prijatel did what any reporter would do: start investigating the disease, how it occurs, how it's treated, and how to keep it from recurring. While she learned that important research on triple-negative breast cancer (TNBC) was emerging, she found a noticeable lack of resources on the disease, which differs from hormone-positive breast cancer in important ways, including prognosis and treatment options. Triple-negative breast cancer disproportionately affects younger women and African-American women-and some forms of it can be more dangerous than other types of breast cancer. But there are many reasons to be hopeful, as Prijatel shows in this book."--Amazon